Durability of induced heat tolerance by short term heat challenge at broilers marketing age. - Soleimani Farjam, Abdoreza; Kasim, Azhar; Alimon, Abdul Razak; Idrus, Zulkifli (Asian Network for Scientific Information, 2008)
A trial was conducted to determine the influence of short term exposure to high ambient temperature at 28 and 35 days of age on deep body temperatures (Tb) and subsequent growth of birds until 42 days of age. A total of 90 day old chicks were reared in stainless steel battery cages and were assigned at random into 18 pens of 5 birds each, with 9 pens containing males and another 9 pens containing females. Three treatment groups, each represented by 3 male and 3 female pens, were represented by T1 without any heat exposure, T2 with heat exposure starting at day 28 and T3 with heat exposure starting at day 35. Heat stress was defined as 180 min exposure to 35±1°C. Tb and body weights were measured at 35, 37 and 39 days of age immediately following heat exposure. Heat stress resulted in higher Tb and Onset of heat stress at 28 days resulted in significantly lower Tb than onset of heat stress at 35 days. Lower Tb in T2 than T3 permitted recovery in body weight at 42 days. Sexes responded similarly to heat stress.